If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -13 = 6y + 19 Reorder the terms: -13 + -2y = 6y + 19 Reorder the terms: -13 + -2y = 19 + 6y Solving -13 + -2y = 19 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -13 + -2y + -6y = 19 + 6y + -6y Combine like terms: -2y + -6y = -8y -13 + -8y = 19 + 6y + -6y Combine like terms: 6y + -6y = 0 -13 + -8y = 19 + 0 -13 + -8y = 19 Add '13' to each side of the equation. -13 + 13 + -8y = 19 + 13 Combine like terms: -13 + 13 = 0 0 + -8y = 19 + 13 -8y = 19 + 13 Combine like terms: 19 + 13 = 32 -8y = 32 Divide each side by '-8'. y = -4 Simplifying y = -4
| -8(x-2)+2=58 | | 9y+12y=63 | | 7x=96-x | | -2(11-4c)=11(c-8) | | 9y+7.7=-4.5 | | 8(-2)=16 | | 5y+7=62 | | 4(x+12)-5=79 | | (x-1)(3x-5)(4x-8)=0 | | X-5=9x-9 | | 1/2=78 | | 7.87=26.25+.5a(2.5) | | 124-5x=40x+19 | | 3x^2-6=6y | | 7.87=26.25+.5(2.5) | | -5(x+7)-42=2-49 | | -5-4=21 | | x-7.7=-4.5 | | 2x^3+5x^2+6x-27=0 | | s-22=-33 | | 3(2x-3)=1-7x | | x^4-0x^3-73x^2-72x=0 | | -6x+4=-8x | | -7x+14=-14x+10 | | 3x-9=84 | | x^2-343=0 | | 10-8x=62-36x | | 3+6=27 | | 5b-(2b+3b-3)+7b= | | 7x-(-4)=4 | | 6x-7=30 | | 8x+1=16x-13 |